Emerging Issues and Challenges to Fiscal Federalism in Pakistan - Rasheed, Rizwana; Rashid, Aamir (International Journal of Business Strategy and Social Sciences, 2022)
After the enactment of the 1973 constitution, the defined roles of federal and provincial governments hit snags when democracy got derailed by two martial laws between 1977 and 2008. The consequences were obvious, as the federation; inter-provincial harmony, and intergovernmental fiscal relations witnessed wide socio-economic development gaps in Human Development Index amongst provinces. The genuine pressing public demand was reflected through a consensus of 7th NFC award during the 18th constitutional amendment by then the democratic government to create harmony in society in general, raising the responsibilities, in particular. The analysis examined the issues like enforcement of fiscal discipline, strengthening the role of the Senate of Pakistan, local governments, barriers to internal trade, absence of fiscal responsibility laws, devolution of further taxes such as GST on retail sales and wholesales needs to be corrected to mitigate dividends of 7th NFC award making fiscal federalism principles a great success in Pakistan.